Effect of some experimental factors on preparation of liquid natural rubber - Khai, Doan Minh; Nhan, Phan Duc (Vietnam Journal of Science and Technology, 2016)
The article presents results of effect of factors comprising the types of irradiation, the concentration of NR solution and the content of hydroperoxide in mixture on photochemical depolymerization of natural rubber. The results showed that the ultraviolet irradiation from the vapor mercury lamps (HSW-250W and HSW-125W) caused the faster rate of depolymerization than the light from HF-500W; increasing concentration of NR in toluene leaded to decrease the rate of depolymerization; and as the content of hydroperoxide increased the rate of depolymerization was faster. Additionally, the IR spectra, 13C-NMR of products were determined and showed that the cis-1,4-isoprene structure has not been changed and there was the presence of hydroxyl-terminated groups and a few epoxy groups in chains.